Analysis of Risk Profile, Good Corporate Governance, Earnings, and Capital (RGEC) in Syariah Commercial Banks and Conventional Commercial Banks - Oyong Lisa; Bambang Hermanto (Universitas Pendidikan Ganesha, 2020)
Banks play a role in collecting public funds because banks are institutions that are trusted by the community from various parties in placing funds safely. This study aims to analyze the differences in financial performance by using RGEC consisting of risk profile, good corporate governance, earnings, and capitals between syariah commercial banks and conventional commercial banks. The analytical technique uses independent sample t-test. The result of the analysis shows that there is a difference of NPL between syariah bank and conventional bank. This shows that conventional commercial banks are better at covering the risk of default of credit repayment by debtors than syariah commercial banks. There is an LDR difference between syariah commercial banks and conventional commercial banks. This shows that conventional commercial banks have a slightly better liquidity level compared to syariah commercial banks. The LDR ratio is too large to indicate the lower ability of the bank's liquidity. There is no GCG difference between syariah commercial banks and conventional commercial banks. This shows that both groups of banks have implemented good corporate governance so that internal management goes according to what is planned. There is a difference of ROA between syariah commercial banks and conventional commercial banks. This shows that the ability of conventional commercial banks has better ability in obtaining net profit with the use of all assets owned by the bank compared to syariah commercial banks. There is no CAR difference between syariah commercial banks and conventional commercial banks. This shows that both groups of banks have met Bank Indonesia's requirements as a sound bank.